Sentiment Towards Social Media Politeness Ambassadors: A Case Study Using the Naive Bayes Method - Fikri, Ridho Ahmad; Muliono, Rizki (Universitas Medan Area, 2025)
Social media has had a significant impact on modern society, serving as a primary platform for sharing information and opinions. One intriguing phenomenon is the viral case of a female police officer, Putri Cikita, who earned the title